Electromagnetic fields for biofouling mitigation in reclaimed water distribution systems. (15th April 2020) - Xiao, Yang; Seo, Youngwoo; Lin, Yufei; Li, Lei; Muhammad, Tahir; Ma, Changjian; Li, Yunkai
Abstract: Biofouling is ubiquitous in reclaimed water distribution systems and causes various industrial, economic, and health issues. This paper investigated the anti-biofouling efficacy of electromagnetic fields (EMFs) for agricultural emitters used for two types of reclaimed water. 16S rRNA gene sequencing and X-ray diffraction were applied to determine the microbial communities and mineral compositions in biofilms. The obtained results revealed that EMF treatment significantly changed the bacterial communities and reduced their diversities in biofilm by affecting water quality parameters. Network analysis results indicated that EMFs were detrimental to the co-occurrence patterns of mutualistic relationships among bacterial species, destroyed the connectivity and complexity of the networks, and inhibited biofilm formation [decreased total biomass and extracellular polymeric substance (EPS) content]. EMF treatment could also decrease the deposition of mineral precipitates, reducing the carbonate and silicate content in biofilm. The decrease of EPS content appeared to reduce biofilm-induced mineral crystallization, while the ion precipitations accelerated by EMFs caused an erosive effect on biofilm. The results demonstrated that EMF treatment is an effective, chemical-free, and anti-biofouling treatment method with great potential for biofouling control in reclaimed water distribution systems. Graphical abstract: Image 1 Highlights: Electromagnetic fields (EMFs) effectively controlled the biofouling in pipelines. EMFs changed the bacterial communities and reduced their diversities in biofilm. EMFs were detrimental to mutualistic relationships among bacterial species. EMF treatment drastically decreased the deposition of mineral precipitation.